"Did I make the right decision?": The difficult and unpredictable journey of being a surrogate decision maker for a person living with dementia. (July 2019) - Fetherstonhaugh, Deirdre; McAuliffe, Linda; Shanley, Christopher; Bauer, Michael; Beattie, Elizabeth
Many people living with dementia eventually lose the capacity to make their own decisions and will rely on another person – a surrogate decision maker – to make decisions on their behalf. It is important – especially with the increasing prevalence of dementia – that the role of surrogate decision maker is understood and supported. This qualitative study explored the experiences of 34 surrogate decision makers of persons living with dementia in Australia. Face-to-face and telephone interviews were conducted over six months in 2014. Five themes were identified: becoming the only – or main – surrogate decision maker; growing into the role of surrogate decision maker; dealing with the stress of making decisions; having to challenge healthcare professionals; and getting support – or not – from family members. An overarching construct tying the themes together is the description of the participants' experience as being on a difficult and unpredictable journey. Healthcare professionals can provide support by acting as empathic guides on this journey.